Clinical and molecular features of 66 patients with musculocontractural Ehlers−Danlos syndrome caused by pathogenic variants in CHST14 (mcEDS-CHST14). Issue 9 (23rd November 2021) - Minatogawa, Mari; Unzaki, Ai; Morisaki, Hiroko; Syx, Delfien; Sonoda, Tohru; Janecke, Andreas R; Slavotinek, Anne; Voermans, Nicol C; Lacassie, Yves; Mendoza-Londono, Roberto; Wierenga, Klaas J; Jayakar, Parul; et al.
Abstract : Background: Musculocontractural Ehlers−Danlos syndrome is caused by biallelic loss-of-function variants in CHST14 (mcEDS- CHST14 ) or DSE (mcEDS- DSE ). Although 48 patients in 33 families with mcEDS- CHST14 have been reported, the spectrum of pathogenic variants, accurate prevalence of various manifestations and detailed natural history have not been systematically investigated. Methods: We collected detailed and comprehensive clinical and molecular information regarding previously reported and newly identified patients with mcEDS- CHST14 through international collaborations. Results: Sixty-six patients in 48 families (33 males/females; 0–59 years), including 18 newly reported patients, were evaluated. Japanese was the predominant ethnicity (27 families), associated with three recurrent variants. No apparent genotype–phenotype correlation was noted. Specific craniofacial (large fontanelle with delayed closure, downslanting palpebral fissures and hypertelorism), skeletal (characteristic finger morphologies, joint hypermobility, multiple congenital contractures, progressive talipes deformities and recurrent joint dislocation), cutaneous (hyperextensibility, fine/acrogeria-like/wrinkling palmar creases and bruisability) and ocular (refractive errors) features were observed in most patients (>90%). Large subcutaneous haematomas, constipation, cryptorchidism, hypotonia and motor developmental delay were also common (>80%). Median ages at the initial episode of dislocation or large subcutaneous haematoma were both 6 years. Nine patients died; their median age was 12 years. Several features, including joint and skin characteristics (hypermobility/extensibility and fragility), were significantly more frequent in patients with mcEDS- CHST14 than in eight reported patients with mcEDS- DSE . Conclusion: This first international collaborative study of mcEDS- CHST14 demonstrated that the subtype represents a multisystem disorder with unique set of clinical phenotypes consisting of multiple malformations and progressive fragility-related manifestations; these require lifelong, multidisciplinary healthcare approaches.